A Diagnosis Missed for Several Years- Wegener’s Granulomatosis - Paudyal, B P; Pantha, S; Ranjitkar, N; Manandhar, A; Arjyal, A (Kathmandu University Medical Journal, 2012)
Wegener’s granulomatosis is a form of systemic vasculitis of small to medium sized vessels and affects upper respiratory tract, lungs and kidneys along with various organs. It causes necrotizing granulomatous inflammation of the affected parts and presents with positive antineutrophil cytoplasmic antibodies in more severe forms. Being a systemic disease with the potential to affect any organ-systems with a wide range of clinical presentations, it is associated with a risk of delay in diagnosis with resultant setback in institution of appropriate treatment. Confusion may arise due to an extent of histological similarity between Wegener’s granulomatosis and the more prevalent tuberculosis, both causing granulomatous inflammation of the affected parts. Here, we present two cases of this rare disorder where the diagnosis was missed for several years in the beginning causing a delay in institution of specific therapy which led to the development of complications. DOI: http://dx.doi.org/10.3126/kumj.v9i3.6309 Kathmandu Univ Med J 2011;9(3):218-21